Nexus between healthcare financing and output per capita: Analysis of countries in ECOWAS sub-region - Oluchukwu F. Anowor; Hyacinth E. Ichoku; Vincent A. Onodugo (Cogent Economics & Finance, 2020)
The performances of African countries particularly in West African Sub- region on global-human development indices had been abysmal over the years and have worsened in the face of COVID-19 pandemic. This is a source of concern to scholars. Expenditure on health and education are recognized by experts as key predictors of human capital development. The latter is theoretically adjudged as a major driver of socio-economic development. This study investigated the relation- ship between health financing and economic performance (proxied by per capita GDP) among the 15 member countries of Economic Community of West African States (ECOWAS). Data spanning the period 1985-2017 were used and Panel Autoregressive Distributive Lag (PARDL) technique was adopted for the analysis. Results show that both private and public expenditures on healthcare were statistically significant to grow output per capita in the long-run. Further findings also suggest that other socio- economic covariates that affected the outcome of aggregate economic performance like price level of capital formation and population growth rate implicitly affected output per capita in the Sub-region. Recommendation points to all critical stake- holders to show more commitment and allocate more resources towards improved health care in the Sub-region if the cycle of stunted economic development will be broken.
Keywords: F15; H51; H53; H75; I12; I190; Q56; 330; ECOWAS; healthcare financing; Human capital; output per capita; panel ARDL